2022
DOI: 10.3389/ti.2022.10375
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Kidney Transplant Recipients With Diabetes Mellitus: A Propensity Score Matching Analysis

Abstract: Kidney transplant recipients present higher rates of pre-existing comorbidities, in particular diabetes mellitus (DM), hypertension, and cardiac disease. We aimed to verify the main risk factors related to DM that contribute to COVID-19 progression and mortality in a kidney transplant setting. From March to August 2020, we evaluated 300 kidney transplant recipients affected by COVID-19. We used propensity score matching (PSM) to estimate the impact of DM on COVID-19. After matching, all baseline characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…In a study of 3,854 patients, glycemic levels greater than >170 mg/dL were also associated with worse outcomes in COVID-19, including an increase in intubation rate (OR = 15.6) and mortality (OR = 3.6), longer hospitalization time, and increased risk for developing ARDS (OR = 9.3) [28]. Using propensity-score matching, our group also documented that higher previous fasting blood glucose was associated with worse outcomes on KTRs independently of DM status [29]. As SARS-CoV-2 induces adipose tissue dysfunction by binding to ACE2 receptor [8], the reduction of adiponectin and adiponectin/leptin ratio is associated with the increase in type I interferon signaling pathway and activation of the innate immune response, which leads to insulin resistance and, consequently, hyperglycemia [28].…”
Section: Discussionmentioning
confidence: 51%
“…In a study of 3,854 patients, glycemic levels greater than >170 mg/dL were also associated with worse outcomes in COVID-19, including an increase in intubation rate (OR = 15.6) and mortality (OR = 3.6), longer hospitalization time, and increased risk for developing ARDS (OR = 9.3) [28]. Using propensity-score matching, our group also documented that higher previous fasting blood glucose was associated with worse outcomes on KTRs independently of DM status [29]. As SARS-CoV-2 induces adipose tissue dysfunction by binding to ACE2 receptor [8], the reduction of adiponectin and adiponectin/leptin ratio is associated with the increase in type I interferon signaling pathway and activation of the innate immune response, which leads to insulin resistance and, consequently, hyperglycemia [28].…”
Section: Discussionmentioning
confidence: 51%
“…Tighter blood glucose control (≤140 mg/dL) might improve outcomes in COVID‐19 critically ill patients 28,29 . Poor glycaemic control was also indicative of COVID‐19 burden in kidney transplant recipients 30 . However, it is unclear whether COVID‐19 can affect the human pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Poor glycaemic control was also indicative of COVID-19 burden in kidney transplant recipients. 30 However, it is unclear whether COVID-19 can affect the human pancreas.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Even if diabetes is a major comorbid condition in patients hospitalized with COVID-19, the effect of the pandemic on the number and outcome of KT recipients with diabetes requires further investigations 10–12. A recent meta-analysis concluded that KT recipients are at higher risk of severe complications and death from COVID-19 than the general population 11.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis concluded that KT recipients are at higher risk of severe complications and death from COVID-19 than the general population 11. Furthermore, KT recipients with diabetes have been reported to have a higher risk of mortality from COVID-19 than those without diabetes (24% vs 13%, p=0.02) 12…”
Section: Introductionmentioning
confidence: 99%